Leading authentically- a prosocial engagement model for middle level bureaucrats in Malaysia - Ahmad, Hal Mahera (2023)
In Malaysia, several reports indicate that leaders in the public sector are expected to be value-driven, authentic and empower their staff to make better decisions in order to promote positive organisational behaviour. In this regard, much attention has been given to the study of specific leadership styles such as transformational leadership and servant leadership in the context of Malaysian public administration. However, there are very few studies that focus on the influence of authentic leaders on their followers and view leadership as a collaborative process. Therefore, this study examines the behaviour of middle-level bureaucrats through four factors: sustainable authentic leadership (SAL), prosocial behaviour (PSB), public service motivation (PSM) and subjective well-being (SWB). Based on self-determination theory (SDT), authentic leadership theory (ALT) and the contingency model, this study assumes that middle-level bureaucrats can engage in prosocial behaviour when they are exposed to authentic leaders, when they are motivated to serve and when they feel good. All these factors and theories are interwoven and form a model for prosocial engagement.